Occupational exposure to chromium(VI) compounds - Jolanta Skowroń; Katarzyna Konieczko (Nofer Institute of Occupational Medicine, 2015)
This article discusses the effect of chromium(VI) (Cr(VI)) on human health under conditions of acute and chronic exposure in the workplace. Chromium(VI) compounds as carcinogens and/or mutagens pose a direct danger to people exposed to them. If carcinogens cannot be eliminated from the work and living environments, their exposure should be reduced to a minimum. In the European Union the proposed binding occupational exposure limit value (BOELV) for chromium(VI) of 0.025 mg/m³ is still associated with high cancer risk. Based on the Scientific Commitee of Occupational Exposure Limits (SCOEL) document chromium(VI) concentrations at 0.025 mg/m³ increases the risk of lung cancer in 2-14 cases per 1000 exposed workers. Exposure to chromium(VI) compounds expressed in Cr(VI) of 0.01 mg Cr(VI)/m3 is responsible for the increased number of lung cancer cases in 1-6 per 1000 people employed in this condition for the whole period of professional activity. Med Pr 2015;66(3):407-427